2022
DOI: 10.2196/28916
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners’ Attitudes Toward Artificial Intelligence–Enabled Systems: Interview Study

Abstract: Background General practitioners (GPs) care for a large number of patients with various diseases in very short timeframes under high uncertainty. Thus, systems enabled by artificial intelligence (AI) are promising and time-saving solutions that may increase the quality of care. Objective This study aims to understand GPs’ attitudes toward AI-enabled systems in medical diagnosis. Methods We interviewed 18 GPs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 80 publications
(106 reference statements)
2
94
0
1
Order By: Relevance
“…For example, 75% of 487 pathologists from 59 countries were enthusiastic about the progress of AI ( 11 ); 77% of 1271 dermatologists from 92 countries agreed that AI would improve dermatologic practice ( 19 ). Similar positive opinions also existed among radiologists ( 22 , 23 , 25 , 29 , 33 , 39 , 47 , 48 , 53 , 55 , 61 ), gastroenterologists ( 24 , 35 ), general practitioners ( 28 , 62 ), psychiatrists ( 59 , 63 ), ophthalmologists ( 23 , 50 ). Additionally, in 14 studies reporting use intentionality, more than 60% respondents in 10 (71.43%) studies were willing to incorporate AI into their clinical practice ( 17 , 21 , 26 , 34 , 36 , 44 , 49 , 55 , 56 , 61 ).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…For example, 75% of 487 pathologists from 59 countries were enthusiastic about the progress of AI ( 11 ); 77% of 1271 dermatologists from 92 countries agreed that AI would improve dermatologic practice ( 19 ). Similar positive opinions also existed among radiologists ( 22 , 23 , 25 , 29 , 33 , 39 , 47 , 48 , 53 , 55 , 61 ), gastroenterologists ( 24 , 35 ), general practitioners ( 28 , 62 ), psychiatrists ( 59 , 63 ), ophthalmologists ( 23 , 50 ). Additionally, in 14 studies reporting use intentionality, more than 60% respondents in 10 (71.43%) studies were willing to incorporate AI into their clinical practice ( 17 , 21 , 26 , 34 , 36 , 44 , 49 , 55 , 56 , 61 ).…”
Section: Resultsmentioning
confidence: 52%
“…Thirty-five included studies mentioned the knowledge level of physicians or medical students on clinical AI, of which 26 (74.29%) showed that participants lacked basic knowledge ( 16 19 , 23 , 25 , 26 , 28 46 ). Many physicians felt that the current training and educational tools, provided by their departments, were inadequate ( 47 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…One uses an online survey to poll healthcare practitioners in image-driven medical disciplines 5 . Another interviews 18 general practitioners on their views on AI 6 . Optimism and concern emerged from these works.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Whilst we did not directly assess PCPs attitudes towards our e-triage tool, other studies have examined their attitude towards AI and telemedicine more generally. 36 , 37 One study highlights some existential anxiety from PCPs towards AI and also feeling threated by AI technology, however, another study found PCP's largely have positive intentions to use telemedicine and e-triage tools in the future. 36 Whilst this reluctance could pose some difficulties in implementing our chatbot tool, Pikkemaat et al suggest that empowering PCP's self-efficacy towards the use of digital tools is key.…”
Section: Discussionmentioning
confidence: 99%